Potential Application of RES and Underground H2 Storage in Abandoned Mines - Antonis Peppas; Sotiris Kottaridis; Chrysa Politi (Materials Proceedings, 2023)
Mining operations, as with all industrial operations, have a significant impact on the environment both through the generation of waste and through landscape change. In view of this, pioneering and sustainable post-mining technologies are demanded to reduce environmental impact. Clean energy can be part of the solution, with emphasis on the penetration of renewable energy sources (RES) for the mitigation of greenhouse gases. RES production is inherently fluctuating, at times being insufficient while others creating energy surpluses. Converting a mining site into a parallel renewable energy generation facility can provide new job opportunities and economic value, as well as contribute to a more secure energy supply. Abandoned mines present a viable option for the installation of such systems, exploiting their underground facilities for safe storage. In this regard, the underground facilities can be exploited for green hydrogen (H2) energy storage systems to be used on-site in times of RES deficits. Underground H2 storage has many advantages over surface storage, including safer storage, smaller footprints, a larger storage capacity, and a lower cost. The re-use of pre-existing infrastructure and land availability for deploying solar parks also offers innovative ways to generate clean energy. This study examines the potential of repurposing abandoned mines in the form of renewable energy generation facilities in order to improve their environmental impact and move quickly towards sustainable and innovative mining throughout Europe.